Assessment of life Quality index among patients with acne vulgaris in a tertiary care hospital, Karamsad, Gujarat: A cross-sectional study - UdayShankar Singh; Pragya Nair; Darshna Sarvaiya; Aditya Dodiya; Aadil Cyclewala; Abhishek Patel; Ami Atodariya (Indian Association of Preventive and Social Medicine, 2021)
Introduction: Acne Vulgaris affects nearly 85% of adolescents. Patients with acne shown to have social, psychological, and emotional impairments. Objective: To identify the psychosocial impacts on healthrelated objects of life. Method: This was a hospital-based, cross-sectional study done at rural tertiary care teaching hospital (Shree Krishna hospital) from October 2019 to November 2019 at Karamsad, Gujarat. Patient aged more than15 years with acne vulgaris were included in the study. According to our inclusion criteria, total 152 patients were included in the study. Grading of Acne vulgaris and its sequelae was done by dermatologists and Quality of Life (QoL) was assessed by using the Dermatology Life Quality Index (DLQI) questionnaire. Results: Most cases (51.97%) were among 15-20 years. The study population included 61(40%) cases with females exceed males. Facial acne was the most common (64.47%). Acne scars were seen in 85.52% of cases. Also, acne scars were more common in males (45%) than females (40%). On interpreting dermatology life quality index score, it was found that 99 % of patients had elevated DLQI scores and Mean DLQI score was 3.05. Conclusion: This study showed a significant impairment of QoL in acne vulgaris patients. Quality of life worsened with the advancement in age, in chronic acne (longer duration of disease), and increase in severity of acne and the presence of post-acne hyperpigmentation.